The Influence of Junior High School Students' Musical Preferences on the Learning of Basic Music Theory - Novrizal, Ricko Salza; Nandiyanto, Asep Bayu Dani; Kurniawan, Tedi; Bilad, Muhammad Roil (Universitas Pendidikan Indonesia (UPI), 2022)
At this time, many types of music emerged and exposure to them was helped by the rapid information received from social media. This research aims to determine whether different musical preferences affect the learning of basic music theory in junior high school students. This research method uses quantitative research. The result of this study is that there are differences in results between students with different musical preferences. Students with rock music preferences experienced a change in knowledge of musical elements from 10 to 70% and students with pop music preferences from 44 to 67%. Students with rock music preferences experienced bigger and more drastic changes, it was because the population with rock music preferences was less than pop music preferences.